Culturable endophytic fungal assemblages from Styrax sumatrana and Stryax benzoin and their potential as antifungal, antioxidant, and alpha-glucosidase inhibitory resources - Elfiati, Deni; Faulina, Sarah Asih; Rahayu, Laras Murni; Aryanto, Aryanto; Dewi, Rizna Triana; Rachmat, Henti Hendalastuti; Turjaman, Maman; Royyani, Mohammad Fathi; Susilowati, Arida; Hidayat, Asep (Frontiers in Microbiology, 2022)
Benzoin resin, produced by the native Indonesian trees Styrax sumatrana and Styrax benzoin, has been incorporated into medical practices to treat wounds, erythema, and many others conditions for centuries. Endophytic fungi that reside within medicinal plants have antimicrobial, antioxidant, and α-glucosidase inhibitory capacities, contributing to plant health and derivative products. In this study, we determined the antifungal, antioxidant, and α-glucosidase inhibitory capacities of endophytic fungal isolates from three different tissues (leaves, bark, and stems) of S. sumatrana and S. benzoin trees. The genera of fungal isolates were determined by phylogenetic analysis of internal transcribed spacer sequences. A total of 58 fungal isolates were classified into 15 different fungal genera from eight taxonomic orders — Hypocreales, Botryosphaeriales, Glomerellales, Diaphortales, Pleosporales, Eurotiales, Xylariales, and Mucorales — with a pattern of host species specificity. Among these isolates, Trichoderma sp. 6407 consistently exhibited high inhibition of the growth of plant pathogens Fusarium sp., Trichoderma viride, and Aspergillus niger. With respect to antioxidant activity, Phyllosticta sp. 6454 consistently showed 2,2-diphenyl-1-picrylhydrazyl inhibition (37.59 ± 0.05%), 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid)-based antioxidant activity (25.04 ± 0.27 mgTE/g), and α-glucosidase inhibitory activity (52.15 ± 10.08%). Neopestalotiopsis sp. 6431 was notably potent in 2,2-diphenyl-1-picrylhydrazyl inhibition (49.65 ± 0.80%), ferric reducing antioxidant power-based antioxidant activity (197.49 ± 8.65 mgTE/g), and α-glucosidase inhibitory activity (52.88 ± 4.93%). This study revealed that Trichoderma sp. 6407, Phyllosticta sp. 6454, and Neopestalotiopsis sp. 6431 exhibited antifungal, antioxidant, and α-glucosidase inhibitory activities.